2017
DOI: 10.1002/2017ms001099
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Modeling on a Mesh With Resolution Following the Local Rossby Radius

Abstract: We discuss the performance of the Finite Element Ocean Model (FESOM) on locally eddy‐resolving global unstructured meshes. In particular, the utility of the mesh design approach whereby mesh horizontal resolution is varied as half the Rossby radius in most of the model domain is explored. Model simulations on such a mesh (FESOM‐XR) are compared with FESOM simulations on a smaller‐size mesh, where refinement depends only on the pattern of observed variability (FESOM‐HR). We also compare FESOM results to a simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 32 publications
3
86
0
Order By: Relevance
“…This increase is especially large on our quasi‐regular 1/4° mesh where the increase in mean velocities with backscatter is substantial, necessitating a smaller time step to match the CFL stability criterion. On other FESOM2 meshes with resolution varying in wider limits (e.g., Sein et al, ), the time step will be smaller to begin with, since it has to follow the CFL limit of the smallest triangles in the mesh. There, a time step of 10 min is not unusual even for globally relatively coarse meshes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase is especially large on our quasi‐regular 1/4° mesh where the increase in mean velocities with backscatter is substantial, necessitating a smaller time step to match the CFL stability criterion. On other FESOM2 meshes with resolution varying in wider limits (e.g., Sein et al, ), the time step will be smaller to begin with, since it has to follow the CFL limit of the smallest triangles in the mesh. There, a time step of 10 min is not unusual even for globally relatively coarse meshes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…These models are usually either coarse with a resolution of about 1° and lower (Taylor et al, ), in which case, all eddy effects are parametrized, or they are eddy permitting with a resolution between about 1/3° and 1/10° (Haarsma et al, ). To simulate eddies with some degree of realism, a resolution of 1/10° or even higher—especially in the very high latitudes and in some areas on the continental shelves—is required: Hallberg () suggests that a resolution with at least 2 grid points per deformation radius is needed, but Sein et al () demonstrated that even this is not necessarily sufficient. Thus, fully resolved simulations of the eddy field are computationally extremely costly, usually too costly to run them as part of climate models for decades to centuries.…”
Section: Introductionmentioning
confidence: 99%
“…In global ocean climate simulations, the value of unstructured meshes can be more outstanding. One can design meshes with resolution varying continuously in space according to the strength of ocean variability, for example, by considering observed sea surface height variability (Sein et al, 2016) and/or Rossby radius (Sein et al, 2017), to permit or resolve mesoscale eddies in middle to low latitudes. It would be interesting to use this kind of global mesh together with specific mesh refinement in the Arctic Ocean for the purpose of Arctic Ocean studies, as the lower latitude ocean will be better resolved with acceptable increase of computational cost and provide more faithful oceanic linkage with the Arctic Ocean.…”
Section: Unstructured-mesh Modelingmentioning
confidence: 99%
“…The purpose of this study is to demonstrate the capability of E3SM on relatively uniform global meshes that are similar to previous studies with structured ocean model grids. Simulations with more dramatic variations in resolution, like those in Sein et al (), will be explored in future work.…”
Section: Introductionmentioning
confidence: 99%